Renegotiating Boundaries 2007
DOI: 10.1163/9789004260436_010
|View full text |Cite
|
Sign up to set email alerts
|

‘Shadow State’?: Business and politics in the province of Banten

Abstract: syarif hidayat 'shadow state'? Business and politics in the province of Banten Our knowledge of the nature of local political leadership in modern democracies based on systematic comparative scholarship is limited. This makes it difficult to generalise across political systems. […] Political scientists just have been more interested in their own political system, and in interviewing national politicians than in comparative studies of local leaders. (Eldersveld et al. 1995:1.) The informal market role in rulers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…She is the wife of Tubagus Chaeri Wardana, who is the younger brother of Ratu Atut Chosiyah, Banten Governor-later was jailed for two cases of corruption and bribes regarding the procurement of medical equipment to the Chairman of the Constitutional Court, Akil Mochtar. Regardless of what was faced by Chosiyah, one thing that is clear was the map of political power here was still held by the family around them, and this happened in many districts/ counties in Banten Province (Hidayat, 2007;Agustino and Yusoff, 2010). In the early stages of the 2015 political contestation, that influence seemed to cause Airin and Benyamin got supported by six political parties.…”
Section: Resultsmentioning
confidence: 99%
“…She is the wife of Tubagus Chaeri Wardana, who is the younger brother of Ratu Atut Chosiyah, Banten Governor-later was jailed for two cases of corruption and bribes regarding the procurement of medical equipment to the Chairman of the Constitutional Court, Akil Mochtar. Regardless of what was faced by Chosiyah, one thing that is clear was the map of political power here was still held by the family around them, and this happened in many districts/ counties in Banten Province (Hidayat, 2007;Agustino and Yusoff, 2010). In the early stages of the 2015 political contestation, that influence seemed to cause Airin and Benyamin got supported by six political parties.…”
Section: Resultsmentioning
confidence: 99%
“…Many political scholars have thus labelled this political elitism as representing a local oligarchy (Robison and Hadiz, 2004), a local shadow state (Hidayat, 2007), a local aristocracy (Dwipayana, 2004;Savirani, 2004;Klinken, 2010), and local 'bossism' (Savirani, 2004). Nationwide studies conducted by Demos from [2003][2004][2005] show that elites have relatively remained determinant actors in local political processes in which the grass root populations only have narrow a space to actively engage.…”
Section: Power In Indonesian Local Politicsmentioning
confidence: 99%
“…The donation takes form as a loan which should be returned in previously agreed form, period, and amount. Studies conducted by Hidayat [2], [5], [6], [7] found that donations from the businessmen created a shadow state and informal economy. These patterns were found in Demak.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%
“…Those businessmen will have special rights such as political and economy protection [4]. Studies conducted by Hidayat [2], [5], [6], [7] found the presence of funders/political investors causing post-election clientism among economic elites and political elites in some provinces. From that study it was known that local election was interfered with political and business conspiracy, and after elected, the regional head would be more loyal to his political and business clients compared to his constituents.…”
Section: Introductionmentioning
confidence: 99%